A 10-Year Case Series of Surgically Managed Periurethral Masses at a Single Tertiary Care Institution. Issue 11 (November 2020) - Wyman, Allison M.; McDowell, Megan; Prieto, Isabel; Jackson, Elisha; Bassaly, Renee; Ordorica, Raul; Greene, Kristie A.
Abstract : Objective: This study aimed to present the evaluation, diagnoses, and surgical management of symptomatic periurethral masses of women at an academic institution. Methods: This study is an institutional review board–approved retrospective case series of women who presented with a symptomatic periurethral mass and scheduled for surgery within the Department of Urology and Female Pelvic Medicine and Reconstructive Surgery over a 10-year period (October 2003–July 2014). Results: Fifty-nine women (mean age, 46 years; range, 22–73 years) were evaluated during the study period. Final pathology revealed 38 (64%) urethral diverticula and 21 (36%) from other benign etiologies. Of the 38 urethral diverticula, 2 (5%) were associated with adenocarcinoma and 4 (11%) with previous bulking agents. Of the 21 nondiverticula, there were 7 (12%) Skene duct cysts/abscesses, 3 (5%) Gartner duct cysts, 2 (3%) vaginal wall inclusion cysts, 2 (3%) bulking agents, 2 (3%) urethral polyps, and one (2%) of each of the following: leiomyoma, angiomyofibroblastoma, redundant vaginal mucosa epithelium, suture abscess, and encapsulated mesh remnant. Fifty-seven women underwent surgical excision (97%), and 2 elected observation. Most (78%) reported resolution of symptoms after excision. Of the patients surgically managed, 7% had postoperative stress urinary incontinence and 12% had persistent lower urinary tract symptoms. Of the 38 women with urethral diverticula, 17% had recurrence and were more likely to have multiple diverticula (44% vs 8%, P = 0.03). Conclusion: Although urethral diverticulum was the most common cause of a periurethral mass, final pathology revealed a variety of benign diagnoses in more than one-third of cases, demonstrating the importance of a thorough investigation for accurate diagnosis.